Intravascular ultrasound-guided intracranial artery stenting in a patient with recurrent ischemic stroke: a case report - N. V. Zakaryan; E. B. Molokhoev; V. V. Boyarintsev; V. N. Ardashev; D. S. Belkov; A. G. Davtyan; V. R. Kirakosyan; A. S. Pankov (Кардиоваскулярная терапия и профилактика)
Introduction. Currently, there is an active search for approaches to the treatment of patients with intracranial artery (ICA) stenosis and recurrent ischemic stroke with aggressive therapy. To date, evidence has been received of the benefits of ICA stenting in combination with drug therapy. It has been shown that invasive treatment is not inferior in effectiveness and treatment outcomes to therapy. Intravascular ultrasound (IVUS) can provide valuable information regarding the morphology of ICA lesions and improve the outcome of ICA stenting.Description. After successful endovascular thrombus removal, a patient with recurrent acute ischemic stroke underwent elective IVUS-guided stenting of the hard-to-reach communicating and cavernous intracranial segments of the internal carotid artery, which made it possible to assess the detailed morphology and select the optimal stent size.Conclusion. A clinical example demonstrates the IVUS potential in the invasive diagnosis of ICA pathology for stenting or balloon angioplasty. ICA IVUS will provide the necessary information for neurointervention specialists to perform highly effective and optimal endovascular interventions on the ICA, similar to percutaneous coronary intervention. This will also reduce the risk of adverse intra- and postoperative events, and will allow identifying patients at high surgical risk.